Association between Dietary Fiber Intake and Incidence of Depression and Anxiety in Patients with Essential Hypertension - Yuanyuan Liu (MDPI AG, 2021)
(1) Background: Our previous study found that the dietary fiber supplement in patients with hypertension increased SCFA-producers, Bififidobacterium and Spirillum in the gut microbiota, which may be associated with improvement of depression and anxiety through the gut–brain axis. However, only a few studies have explored the association between dietary fiber intake (DFI) and the incidence of depression and anxiety in hypertensive patients. (2) Methods: A cross-sectional survey was conducted in one comprehensive hospital and one community clinic aimed at understanding the status of DFI and the association between DFI and incidences of depression and anxiety in hypertensive patients. Levels of DFI were obtained through a two-24 h diet recall. According to the levels of DFI from low to high, the participants were divided into Q1, Q2, Q3 and Q4 groups. The Reported Outcomes Measurement Information System short form v1.0-Depression 8b and Anxiety 8a were used to assess patients’ levels of depression and anxiety. (3) Results: A total of 459 hypertensive patients were recruited and the daily DFI was 10.4 g. The incidences of hypertension combined with depression and anxiety were 19.6% and 18.5%, respectively. Regression analysis showed statistically significant associations between DFI and depression (B = −0.346, p = 0.001) and anxiety score (B = −0.565, p < 0.001). In logistic regression, after the covariates were adjusted, DFI was associated with the incidence of depression in Q3 (OR 2.641, 95% CI 1.050–6.640) and with that of anxiety in Q1 (OR 2.757, 95% CI 1.035–7.346), compared with Q4. (4) Conclusions: A higher consumption of DF was a protective factor for depression and anxiety in hypertensive patients.